Физика. 10 класс: учебник для средней школы / Г. Я. Мякишев - Мякишев Геннадий Яковлевич (Просвещение, 1988)
Экземпляры: БС (20170828) / Инвентарный номер: РТШ47793 / Сис.шифр: 22.3я72 / Авт.знак: М 99 / ГРНТИ: 29 / ББК: 22.3я72